2015
DOI: 10.31186/jagrisep.14.2.177-188
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Komparasi Usahatani Padi Sawah Pengguna Benih Bersertifikat Dan Benih Non Sertifikat Di Kelurahan Kemumu Kecamatan Arma Jaya

Abstract: This research purposse are to calculate and compare the productivity of land, income, and efficiency between paddy farming using certified seed and paddy farming which uses non-certified seed. The research was conductedin the village of Kemumu with a total sample of 15 farmers certified seed specified users using census method and 22 non-certified seed user farmers were determined using purposive sampling method. Methods of data analysis using quantitative analysis and qualitative (descriptive). The analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…The first option was difficult to implement. Several studies have shown that the use of certified seeds can increase garlic farming productivity (Aldila et al, 2015;Kiloes et al, 2017;Raditya et al, 2015). This study also showed that the use of certified garlic seeds could increase the productivity of garlic farming.…”
Section: Parameter Estimation Of Sample Correction Stochastic Product...supporting
confidence: 55%
“…The first option was difficult to implement. Several studies have shown that the use of certified seeds can increase garlic farming productivity (Aldila et al, 2015;Kiloes et al, 2017;Raditya et al, 2015). This study also showed that the use of certified garlic seeds could increase the productivity of garlic farming.…”
Section: Parameter Estimation Of Sample Correction Stochastic Product...supporting
confidence: 55%
“…The certified seeds lead to no better result than non-certified seeds. The use of noncertified seeds is more profitable, as asserted by [8]. Conversely, the R / C results show the opposite, where R / C from farming using certified rice seeds is higher than noncertified seed yields.…”
Section: Resultsmentioning
confidence: 94%
“…(2-tailed) > 0,05) (Darisman et al, 2020). Ada juga penelitian serupa menunjukkan hasil yang konsiten, pendapatan rata-rata Rp 16.501.384,77/Ha untuk usahatani padi sawah menggunakan benih bersertifikat dan sebesar Rp 10.951.035,29/Ha untuk usahatani padi yang menggunakan benih yang tidak bersertifikat (Raditya et al, 2015).…”
Section: Tabel 3 Responden Berdasarkan Klasifikasi Tingkat Pendidikanunclassified